Developmental defects of the enamel and its impact on the oral health quality of life of children resident in Southwest Nigeria - Morenike Oluwatoyin Folayan; Nneka Maureen Chukwumah; Bamidele Olubukola Popoola; Dada Oluwaseyi Temilola; Nneka Kate Onyejaka; Titus Ayo Oyedele; Folake Barakat Lawal (BMC, 2018)
Abstract Background Developmental defects of the enamel (DDE) increase the risk for diseases that impact negatively on the quality of life. The objective of this study was to compare the oral health quality of life of children with molar-incisor-hypomineralisation (MIH) and enamel hypoplasia; and assess if caries worsened the impact of these lesions on the quality of life. Methods This study recruited 853 6 to 16-years-old school children. They filled the Child-OIDP questionnaire. The MIH, enamel hypoplasia, caries and oral hygiene status was assessed. Poisson regression was used to determine the impact of MIH and enamel hypoplasia on the oral health quality of life, after adjusting for the effect of sex, age, socioeconomic class, oral hygiene and caries status. Results The prevalence of MIH and enamel hypoplasia was 2.9% and 7.6% respectively. There was no significant difference in the mean child-OIDP scores of children with or without MIH (p = 0.57), children with or without enamel hypoplasia (p = 0.48), and children with enamel hypoplasia with and without caries (p = 0.30). Children with enamel hypoplasia and caries had worse outcomes for speaking (p = 0.01). Children with middle (AOR: 2.74; 95% CI: 1.60-4.67; P < 0.01) and low (AOR: 1.75; 95% CI: 1.04-2.95; p = 0.03) socioeconomic status, and those with caries (AOR: 2.02; 95% CI: 1.26-3.22; p = 0.03) had their oral health quality of life negatively impacted. Conclusion MIH and enamel hypoplasia had no significant impact on the overall oral health quality of life of children resident in southwestern Nigeria. However, children with caries and those from middle and low socioeconomic classes had poorer oral health quality of life.